Clinical Symptom Profiles After Mild–Moderate Stroke. Issue 11 (4th June 2019) - Katzan, Irene L.; Schuster, Andrew; Bain, Mark; Lapin, Brittany
Abstract : Background: There is heterogeneity in the severity of domains affected in patients with stroke, resulting in differences in health‐related quality of life (hrQoL). Identifying different clinical profiles of stroke patients may provide a means for selecting patients for tailored interventions to improve hrQoL. Methods and Results: This was an observational study of 496 patients with ischemic stroke or intracerebral hemorrhage seen in a cerebrovascular clinic from October 12, 2015, through June 11, 2018, who completed patient‐reported outcome measures using Patient‐Reported Outcome Measurement Information System (PROMIS) tools within 1 month of stroke. Latent profile analysis identified groups based on PROMIS domain scores—pain, depression, cognitive function, fatigue, social role satisfaction, and physical function—as well as clinician‐reported modified Rankin Scale (mRS). Five distinct profiles were identified. Group 1 ("excellent hrQoL, " n=106) had fewer symptoms in all domains than the general population. Group 2 ("disabled with mixed hrQoL, " n=17) had fewer symptoms than the general population in all domains except social role satisfaction and physical function, despite having moderate disability (median mRS score: 3). Group 3 ("mild limitations with average hrQoL, " n=189) had scores similar to the general population for all domains and minimal disability (median mRS score: 1). Group 4 ("mild limitations with poor hrQoL, " n=152) also had a median mRS score of 1 but had worse scores than group 3 on all domains. Group 5 ("disabled with poor hrQoL, " n=32) had worse symptoms than patients in the other profiles and a median mRS score of 3. Conclusions: Patients with recent stroke have distinct clinical symptom profiles, even with similar levels of clinician‐reported disability. Symptom profiles provide a means of understanding patterns of outcomes in patients with stroke.